1993
DOI: 10.1148/radiology.186.3.8430179
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytomas that do not accumulate metaiodobenzylguanidine: localization with PET and administration of FDG.

Abstract: Many imaging methods can be used to detect pheochromocytoma, but some tumors are not detected with conventional modalities. To explore the possible usefulness of positron emission tomography (PET) after administration of 2-[fluorine-18]-fluoro-2-deoxy-D-glucose (FDG) to localize pheochromocytoma in patients with false-negative scintigrams obtained after administration of metaiodobenzylguanidine (MIBG), FDG was administered and PET was performed in two adult patients with pheochromocytomas that had never been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 0 publications
0
34
0
3
Order By: Relevance
“…One report has concerned the detection of medullary phaeochromocytoma while another has evaluated the role of PET in differentiating indeterminate adrenal mass in patients with cancer [121,283]. No report has as yet dealt with the diagnosis of hyperfunctioning cortical tumours.…”
Section: Adrenalsmentioning
confidence: 99%
See 1 more Smart Citation
“…One report has concerned the detection of medullary phaeochromocytoma while another has evaluated the role of PET in differentiating indeterminate adrenal mass in patients with cancer [121,283]. No report has as yet dealt with the diagnosis of hyperfunctioning cortical tumours.…”
Section: Adrenalsmentioning
confidence: 99%
“…Shulkin et al have reported on two patients in whom metaiodobenzylguanidine failed to demonstrate the tumour [283,284]. FDG PET enabled correct localization of the tumour in both cases with high contrast and should be useful in turnouts that do not accumulate MIBG.…”
Section: Adrenalsmentioning
confidence: 99%
“…Shulkin et al [95] was the first to report the advantages of 18F-FDG imaging in PCCs/PGLs that do not accumulate MIBG. The uptake of 18F-FDG is not related to tumor secretory status; its superiority in malignant PCCs that do not accumulate I 131 or I 123 MIBG has been confirmed [87,96].…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Esse método pode localizar feocromocitomas extra-adrenais não localizados com 131 I MIBG. Entretanto, mais estudos são necessários para a determinação de sua real eficácia 27 . Maurea et al compararam a captação com 131 I MIBG, tomografia computadorizada e ressonância magnética, evidenciando, em pacientes ainda não submetidos à cirurgia do feocromocitoma, sensibilidade de 82% no 131 I MIBG, e de 100% nos dois outros métodos.…”
Section: ) Diagnóstico Anatômicounclassified
“…Os principais riscos na cateterização seletiva são: infarto da glândula adrenal e liberação de catecolaminas pela manipulação do tumor. A localização precisa dos pontos de coleta sanguínea é obtida por meio da flebografia e dosagem de cortisol plasmático 6,9,27,28 . A arteriografia pode ser realizada quando há suspeita de feocromocitoma extra-adrenal ou quando a tomografia não localiza o tumor, mas é um método invasivo pouco utilizado, freqüen-temente precipitando crises hipertensivas 2,29 .…”
Section: ) Diagnóstico Anatômicounclassified